Der Althistoriker Franz Hampl zwischen Nationalsozialismus und Demokratie : Kontinuität und Wandel im Fach Alte Geschichte. - Deglau, Claudia (Philippika - Altertumskundliche Abhandlungen, 2017)
The Austrian ancient historian Franz Hampl (1910-2000) is considered a particularly "critical spirit" of his time, which not only outlines his personality, but also characterizes his work and his work as a professor in Innsbruck (1947-1981). His life and his academic career were shaped by the political upheavals of the 20th century. He was scientifically socialized with Helmut Berve in Leipzig, one of the most influential ancient historians during the Nazi era. The impact of his participation in World War II on his historical thinking can hardly be overestimated. After 1945, Franz Hampl was one of the few ancient historians of his generation who endeavored to restore ancient history.He questioned common historical images, opposed a "glossing over history" and was often at odds with the "communis opinio". On the basis of archival records, Claudia Deglau is the first to comprehensively reconstruct Franz Hampl's academic career and analyze his work and understanding of history over time. By contextualizing Hampl's intellectual biography with the social and (university) political structures as well as the contemporary currents in the subject of ancient history, a comprehensive picture of the development of ancient history in an "age of extremes" is offered on the basis of his individual career.